Hot carriers in halide perovskites : how hot truly? - Lim, Melvin Jia Wei (2020)
Slow hot carrier cooling in halide perovskites holds the key to the development of hot carrier (HC) perovskite solar cells. For accurate modeling and pragmatic design of HC materials and devices, it is essential that HC temperatures are reliably determined. A common approach involves fitting the high-energy tail of the main photobleaching peak in a transient absorption spectrum with a Maxwell-Boltzmann distribution. However, this approach is problematic because of complications from the overlap of several photophysical phenomena and a lack of consensus in the community on the fitting procedures. Herein, we propose a simple approach that circumvents these challenges. Through tracking the broadband spectral evolution and accounting for bandgap renormalization and spectral line width broadening effects, our method extracts not only accurate and consistent carrier temperatures but also other important parameters such as the quasi-Fermi levels, bandgap renormalization constant, etc. Establishing a reliable method for the carrier temperature determination is a step forward in the study of HCs for next-generation perovskite optoelectronics.